Developing CLE in Myanmar-Lessons Learned and Global Guidance - Lasky, Bruce A (The Indonesian Journal of International Clinical Legal Education, 2019)
This paper, Developing CLE in Myanmar: Lessons Learned and GlobalGuidance, is an adaption of an Advocacy Paper entitled The Global Pathand Future of CLE in Myanmar, which merged from findings from morethan three years of BABSEACLEÃ¢â‚¬â„¢s work, often in collaboration with NewPerimeter (DLA PiperÃ¢â‚¬â„¢s global pro bono non-profit affiliate) and HerbertSmith Freehills (HSF) (collectively referred to as the Ã¢â‚¬Å“ConsortiumÃ¢â‚¬Â). TheConsortium worked with eighteen Myanmar university law departmentsto implement Clinical Legal Education (CLE) programmes in partnershipwith diverse stakeholders in Myanmar (2013-Present). The Paperpresents key strategies which the author believes will contribute to thesustainable future of a nationwide CLE programme in Myanmar withinsights and lessons learned that are applicable both regionally andglobally. This timely initiative was undertaken with broad, wide-rangingsupport from the United Nations Development Programme (UNDP), theUnited States Agency for International Development Promoting Ruleof-law Project (USAID PRLP) and other related organisations. This Paperhighlights how drawing on and applying findings from regional andglobal experiences, CLE in Myanmar has grown from its nascent stageinto a young but ever increasing vibrant movement of educational andjustice change and impact. In doing so, this movement is helping tocreate the noteworthy educational justice change and impact, includingits interaction with others in the legal sector, that we are currentlywitnessing. This Paper evaluates the impact of implementing anationwide CLE programme in Myanmar from early 2013 to the present.Simultaneously, the Paper is also a timely resource for planning; todevelop, implement or strengthen CLE programmes in Myanmar andworldwide. It also offers pragmatic recommendations to facilitate theexpansion, institutionalization, and sustainability of CLE in Myanmarand elsewhere.